Teachers' beliefs about diversity: an analysis from a personal and professional perspective - Esther Chiner Sanz; María Cristina Cardona Moltó; José Marcos Gómez Puerta (Springer, 2015)
The purpose of this study was to examine the beliefs that teachers have about diversity and their level of sensitivity towards some topics related to it. Moreover, beliefs were compared according to teachers' personal and professional views and teaching experience. The Personal and Professional Beliefs about Diversity Scales (Pohan and Aguilar, 1999) were administered to a sample of 233 teachers. Results showed highly positive beliefs towards diversity in all its dimensions (cultural, linguistic and social diversity, ability, gender, sexual orientation and religion), especially regarding its personal implications compared to the professional ones. Likewise, it was observed a significant relationship between years of teaching experience and professional beliefs about diversity, so teachers with no school experience showed a higher tolerance than those with teaching experience, mainly in aspects related to cultural, linguistic and social differences, ability and gender. The implications that these results have for educational practice and the need for the development of multicultural education courses that favour an effective teaching are discussed.